Annotated record of the detailed examination of Mn deposits from DSDP Site 86, Leg 10 (Cores 86-8, 86-9) - J Lamar Worzel; W R Bryant; A O Beall; K Dickinson; R Laury; L A Smith; B McNeely; H P Foreman; R Capo (PANGAEA, 1973)
The origin of the Campeche Escarpment in the Gulf of Mexico has been attributed to several causes. Some suggest that the scarp represents a fault scarp, others suggest that its origin is a function of upbuilding and outbuilding likened, in some cases, to that of delta building. Still others suggest that the scarp represents the detrital accumulation seaward of a barrier or reef complex. In order to clarify these possible interpretations, Site 86 was located on a bench at a depth of 780 fathoms in the vicinity of the Campeche Escarpment.
Supplement to: Worzel, JL et al. (1973): Site 86. In: Worzel, J.L.; Bryant, W.; et al., Initial Reports of the Deep Sea Drilling Project, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, X, 25-47, https://doi.org/10.2973/dsdp.proc.10.103.1973